KARAKTERISTIK ELECTRONIC ETHANOL INJECTION PADA MESIN BERSILINDER TUNGGAL - , BAMBANG SULISTYO, SPd, Prof. (Emr). Adhi Susanto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The most energy requirement for Indonesiaâs people are still fulfilled by fossil energy resources. Renewable energy or new energy application for energy supply is very important. Ethanol is one of many energy recourses that can be used. One of the solution is use etanol fuel in motorbike. But that way etanol have the nature of different with the gasoline fuel so difficult to mixed in the form of fluid. Its for that needed a technology which can exploit the etanol in combustion of gasoline motor and mixed in gas phase so that excellence etanol earn application. The research was aimed to develop four-stroke engine by applying Electronic Ethanol Injection System (EEI). The experiment was conducted to recognize influences of ethanol fuel system changes to the engine performances and exhaust gas emission. The results were expected to be useful for automotive industry, mainly for improving the four-stroke engine and reducing air pollution due to its exhaust gas emission. The research used Honda PGM-FI (125 cc) and applied Fuel Injection System designed for Honda Supra X PGM-FI. This technology is injection of etanol into combustion chamber at the same time with the spraying of gasoline fuel by gasoline injector. Mixing that happened in intake manifold will cause the change of combustion characteristic in combustion chamber. The ethanol injector was installed on the intake manifold with in-line toward their gasoline injector. The change of the injection ethanol pressure was 1 bar, 1.2 bar, dan 1.4 bar. The results show that the substitution of the ethanol fuel system has positive impacts to the engine characteristics. In all ethanol pressure variations, there is an acceptable decrease in performance, i.e. in the power down by 1,72 %, and is increasing bsfc 8,89%. The exhaust gas emission were also improved, indicated by 42,54% reduction of CO and 44,48% reduction of HC. The best engine characteristic is obtained from the ethanol injector position with 1 bar.